Diabetes following acute pancreatitis. (August 2021) - Hart, Phil A; Bradley, David; Conwell, Darwin L; Dungan, Kathleen; Krishna, Somashekar G; Wyne, Kathleen; Bellin, Melena D; Yadav, Dhiraj; Andersen, Dana K; Serrano, Jose; Papachristou, Georgios I
Summary: Diabetes represents a group of diseases involving persistent hyperglycaemia. Exocrine disorders of the pancreas are increasingly recognised to cause or precede the onset of diabetes, which in this context is referred to as pancreatogenic or type 3c diabetes. Diabetes, as a sequela of acute pancreatitis, is observed across the spectrum of severity in acute pancreatitis and can be associated with other clinical complications. The pathophysiology of acute pancreatitis-related diabetes is poorly understood, and observations suggest that it is probably multifactorial. In this Review, we discuss the epidemiology, pathophysiology, and management considerations of diabetes following acute pancreatitis, and highlight knowledge gaps in this topic.